Note on the velocity and temperature distributions attained with suction on a flat plate of infinite extent in compressible flow - Young, A. D. (College of Aeronautics, Cranfield, 1947)
The problem considered by Griffith and Meredithl for incompressible flow is here considered for compressible flow, it being assumed that there is no heat transfer by conduction at the plate. Essentially, the method consists of establishing a correspondence between the velocity and temperature profiles for incompressible flow and those for compressible flow, the lateral ordinated being scaled by factors which are functions of the ordinates and of Mach number. The results of calculations covering a range of Mach numbers up to 5.0 are shown in Figs. A and 2.